2009
DOI: 10.1364/oe.17.000747
|View full text |Cite
|
Sign up to set email alerts
|

Influence of imperfections on the insulating and guiding properties of finite Si-inverted opal crystals

Abstract: Abstract:The stability of the photonic properties of Si-infiltrated opals for fabrication disorder is tested with following models of applied imperfections: deviations in radii of spheres, deviations in spheres positions and both of them. The deviations are assumed to be distributed accordingly to the normal law and to the skewed distribution experimentally observed in the process of production of polymer self-assembled crystals. The criteria for the photonic crystals tolerances are evaluated versus the qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…The results obtained are in accordance with the consideration [26] that the photonics-based devices (e.g. frequency filters) do not exhibit in real non-ideal conditions so nice properties as it was expected from the calculations for ideally periodic photonic crystals.…”
Section: Fig 22supporting
confidence: 89%
“…The results obtained are in accordance with the consideration [26] that the photonics-based devices (e.g. frequency filters) do not exhibit in real non-ideal conditions so nice properties as it was expected from the calculations for ideally periodic photonic crystals.…”
Section: Fig 22supporting
confidence: 89%
“…6(a) It has been reported that such a level of fluctuation does not induce a critical degradation of the band-gap effect in the wafer-bonding-based 3D photonic crystals [24,25], whereas it might significantly influence inverted opal structures [26,27]. …”
Section: Analysis Of Fabrication Tolerancementioning
confidence: 99%
“…Polydisperse fluids are very widespread indeed, with examples comprising blood, paint, milk, clay, shampoo, viruses, globular proteins, photonic crystals, pharmaceuticals and even sewage, among several others. [12][13][14][15][16][17][18][19][20][21] The present work investigates how an arbitrary polydisperse fluid in the liquid-gas coexistence region behaves near its liquid-gas critical point (CP). Our development is valid for any number of particle species regardless of the nature of interparticle interactions, and therefore applies to generic multi-component mixtures.…”
Section: Introduction and Overviewmentioning
confidence: 99%